Strategi Komunikasi Pemasaran Melalui Instagram @muspera_kehutanan untuk Meningkatkan Kunjungan Wisatawan di Museum dan Perpustakaan Kementerian Kehutanan - Made Shanty Aurellia; Willy Bachtiar (Lembaga Pengembangan Kinerja Dosen, 2025)
Marketing Communication Strategy through Instagram @muspera_kehutanan to increase tourist visits to the Museum and Library of the Ministry of Forestry aims to describe the promotional methods carried out by the Museum and Library of the Ministry of Forestry on Instagram social media. This type of research uses a descriptive qualitative method using the IMC (Integrated Marketing Communication) Theory with a focus on four implementation patterns: Word of Mouth Marketing, interactive/internet marketing through social media, publicity and public relations, and events & experiences. The results of this study indicate that the strategy used by the Museum and Library of the Ministry of Forestry in promoting educational tourism objects through the Instagram media @muspera_kehutanan is to utilize Instagram and TikTok social media to spread educational, entertainment, and promotional content that is appropriate to the target audience. In addition, the word of mouth strategy also plays a role in increasing visits, with recommendations from previous visitors. Content that is consistently posted on Instagram helps build a positive image of Muspera and increases interaction with the audience. However, challenges such as the lack of cross-promotion with external parties limit the reach of a wider audience. Overall, the marketing communication strategies implemented by Muspera have proven successful in attracting tourist interest, although there are some areas that can still be improved